Microsponsorships: A New Payment Model for Music Distribution - Herrera, Gregory (Trinity College Dublin. Department of Computer Science, 2005)
Today?s music industry on the Internet is dominated by the record companies who charge users to download MP3s. In most cases, users do not have the opportunity to listen to the entire song prior to downloading and purchasing it which means they may end up paying for content that they don?t really like. Since no refund policy exists under the current system, consumer rights are somewhat compromised. Further to this, the record companies profit greatly from each transaction with the artists themselves only receiving a small percentage of the profits. Thus it is clear that the present model for purchasing music from the Internet is restrictive for both artists and consumers. The objective of this dissertation was to design a new model for purchasing music from the Internet that would be less restrictive for artists and users alike. The aim was

to produce a working prototype, namely an MP3 player, that would allow the user, at the click of a button, to donate money directly to the artist they are listening to, and to support their favourite artist. The mechanism of the proposed model is such that when a user listens to a song that they like they can click on a Donate button on the MP3 player which will take them directly to the web site of that particular artist. The web site will contain payment options (in the case of this prototype the online payment system PayPal is used) should the user wish to donate money to the artist. Obviously, such a system is dependant on the artist having payment data stored within the ID3 tag which is located in the MP3. In the working prototype, when this payment data is present in the MP3, the Donate button on the MP3 player is activated. In contrast, if no payment data is contained in the MP3, this button remains inactive. Because this system allows consumers to support artists directly, it takes away the need for the middle man, in this case, the record companies. Consequently, even unknown artists could use the Internet as a platform from which to promote their music. Needless to say, if such a system were to be put into action, it would encounter a strong opposition from record companies. While ethical and copyright issues obviously exist with the above prototype, it does provide an example of a less restrictive model for purchasing music from the Internet.
Keywords: Computer Science